ANALYSIS OF EFFECTIVENESS OF PAVEMENT INFRASTRUCTURE (CASE STUDY: JL. AHMAD YANI PONTIANAK) - Irdasyah, Naufal Fadlurahman; Azwansyah, Heri; Basalim, Said (Jurnal Teknik Sipil, 2023)
This study aimed to determine the effectiveness of pedestrian paths (sidewalks) in the Pontianak Selatan District, precisely on Jalan Ahmad Yani. The sidewalk as a pedestrian path is a space for pedestrians that functions as a means to protect pedestrians from the dangers that come from vehicles using the road. The method used is the survey method and questionnaire method. The data analysis method (Highway Capacity Manual, 1985) is used to obtain pedestrian characteristics.Analysis of survey data used the Likert Scale method to obtain the level of pedestrian comfort and safety based on respondents' perceptions. The results of calculating the effectiveness of the sidewalks on Jalan Ahmad Yani obtained for zones A, B, and C are 17.35 m2/person, 7.75 m2/person, and 30.39 m2/person. Based on the calculation of the pedestrian characteristics of the three road sections, the pedestrian path service level is obtained with standard A or LOS A.The results from respondents obtained 11 good categories and two suitable enough types based on the calculation of the percentage of comfort level categories. The level of data reliability reached 0.853 based on SPSS statistics 2016. The results of this study indicate that the pedestrian path (sidewalk) is an excellent facility for pedestrians to exercise and relax in Pontianak Selatan District.